Reliability of AC thick-film electroluminescent lamps - Vlaskin, V.; Vlaskina, S.; Berezhinsky, L.; Svechnikov, G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The reliability of AC thick-film EL devices has been studied. The AC thickfilm
EL devices were fabricated by Novatech Inc. using the industrial print screen
technology. The analysis of reasons for failure has been proposed. The dependence of EL
lamp parameters on physical properties of the device EL layers was found. Our analysis
of the breakdown spot showed that improvement of reliability can be reached using the
additional dielectric layer between the phosphor layer and transparent electrode, high
concentration of phosphor powder 70 % and binder 30 %, balanced resistance between
the electric circuit and EL lamp. The thickness of the phosphor layer was equal to H =
(1 + √3/2)D (hexagonal packing), where D is the mean diameter of phosphor particles.
The reliability dependence of EL lamp on a water adsorption property of packaging
material was revealed.